PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA - MARCEL HAGGAI (Jurnal Akademika, 2018)
This study aims to determine and analyze the influence of Leadership Style and Organizational Culture on Employee Performance through Job Satisfaction at Bank Mandiri Depok Area. The method used in this research is quantitative descriptive research with causality research. The population in this study were employees of Bank Mandiri Area Depok which amounted to 473 employees. The number of samples based on the Slovin formula so as to obtain a sample of 217 employees.The result of this research is expected that leadership style influence to job satisfaction of employees. Organizational culture affects employee job satisfaction. Leadership style influence on employee performance. Organizational culture affects employee performance. Job satisfaction affects employee performance.Keyword: leadership style, organizational culture, job satisfaction, employee performance.